Impact of IMT504 on the immune system of female non-obese diabetic (NOD/Ltj) mice - Bianchi, Stefania (2017)
Immunomodulatory oligonucleotide IMT504 (IMT) improved glycemia, beta cell function, and reduced leukocyte islet infiltration in spontaneous autoimmune diabetic mice (female NOD/Ltj). We analyzed the effects of IMT on immune parameters.